Early stage minimally invasive procedures reduce perihematomal MMP-9 and blood-brain barrier disruption in a rabbit model of intracerebral hemorrhage. (1st July 2013) - Wu, Guofeng; Sun, Shujie; Long, Xianyue; Wang, Likun; Ren, Siying
Abstract : Introduction: The effects of performing a minimally invasive procedure at different stages after intracerebral hemorrhage (ICH) on perifocal MMP-9 expression and blood-brain barrier (BBB) permeability were evaluated. Methods: Thirty-six rabbits were randomly distributed into a normal control group (NC group, six rabbits), a model control group (MC group, six rabbits), and a minimally invasive group (MI group, 24 rabbits). A model of ICH was established in the MC and MI groups. In the MI group, the intracerebral hematoma was evacuated by stereotactic minimally invasive procedures over 6 hours (six rabbits), 12 hours (six rabbits), 18 hours (six rabbits), and 24 hours (six rabbits), following successful induction of ICH. All animals were sacrificed within 48 hours after the hematoma was surgically evacuated. A neurological deficit score was determined, and the perihematomal MMP-9 level and the BBB permeability were measured. Results: The neurological deficit score, the perihematomal MMP-9 level, and the BBB permeability of the MI group were decreased significantly compared with the MC group. Performing the MI procedure 6-12 hours after ICH showed the most significant decrease in MMP-9, BBB permeability, and neurological deficit score. Conclusion: The optimal time window of performing MI procedures for the intracerebral hematoma evacuation might be within 6-12 hours after hemorrhage.